The psychological adjustment of West African men post myocardial infarction: a counselling psychology study using interpretative phenomenological analysis - Coventry, Shirley (2011)
Introduction: Increasingly effective medical practices and treatments for Coronary Heart Disease (CHD) have resulted in a growing need for Cardiac Rehabilitation programmes to improve morbidity and reduce further mortality. However, poor service uptake figures for the ethnic minority groups, especially of West African men, have highlighted the need for research, as this appears to be an unexplored area, and the National Service Framework (2000) also recognised the ethnic groups as a `special' interest focus, requiring specific attention. This Counselling Psychology study, therefore, aimed to explore the post heart attach experience of these men to ascertain if their psychological adjustment may be deterring service uptake. More specifically this study attempts to investigate the adjustment experience of these men (their cognitive appraisal and coping strategies), seeking to assist in explaining their low attendance of health programmes, and highlight any specific needs that the cardiac teams and psychological services must address.